2020
DOI: 10.1177/2041419620918883
|View full text |Cite
|
Sign up to set email alerts
|

Peak overpressure and impulse due to diffraction over a cylinder and/or multi-reflection of a shock wave in structural design- Part I

Abstract: The design and planning of structural components, such as columns, to resist blast loads is a complex task. Often standard free-field blast loads, specified in design codes or other literature, are used for the analysis of the object. These loads are then further increased or decreased depending on the topology of the surrounding geometry (Mach-Stem), the shape of the impacted object itself, and blast wave reflection. However, most of these research works focus purely on the assessment of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Table 3 displays the input parameters that were considered, sub-divided into 5 groups, A through E. These combinations have been carefully selected to cover a wide spread of blast wave properties such as overpressure, specific impulse, positive phase duration, and importantly, the shock wave velocity, which has a direct effect on the formation of vortices in the disturbed wake region (Hahn et al, 2021; Niollet et al, 2015; Ritzel et al, 2018). Group E has been included for comparing the effect of each of the cylinder sizes under consideration (in groups A–D) for a given blast wave intensity and obstruction ratio.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 displays the input parameters that were considered, sub-divided into 5 groups, A through E. These combinations have been carefully selected to cover a wide spread of blast wave properties such as overpressure, specific impulse, positive phase duration, and importantly, the shock wave velocity, which has a direct effect on the formation of vortices in the disturbed wake region (Hahn et al, 2021; Niollet et al, 2015; Ritzel et al, 2018). Group E has been included for comparing the effect of each of the cylinder sizes under consideration (in groups A–D) for a given blast wave intensity and obstruction ratio.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Therefore, mitigating a blast wave by means of wave interactions described previously may also be evaluated reliably using numerical simulations. Hahn et al (2021) numerically characterized the pressure and impulse changes downstream of a blast wave-circular pole interaction. The explosive charge masses were varied to generate a range of scaled stand-off distances.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when the distance between the outflow boundary and the charge is greater than 100 mm, the outflow boundary on one side of the charge does not significantly affect pressure distribution on the other side. Previous study has shown that the influence of outflow boundaries was found to only extend 10-20 elements (Hahn et al, 2020). Subsequent numerical models far exceed these requirements.…”
Section: Numerical Modelmentioning
confidence: 98%
“…For bomb attacks in urban environments, blast loads on structures depend on the geometric shape of structures and blast waves. Previous studies on blast loads mostly focus on spherical charges and flat targets, some design manuals give blast loads on the surface of cuboids (Baker, 1973; Defense, 2008; Henrych and Abrahamson, 1980; Hyde, 1991; Kingery and Bulmash, 1984), a probabilistic blast load model for domes has been proposed based on extensive tests (Qi et al, 2020; Zhi et al, 2019), detailed experimental data on blast loads of cylindrical structures for direct verification of numerical models are not available (Hahn et al, 2020; Kristoffersen et al, 2021; Qasrawi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%